Homoeologous exchange is a major cause of gene presence/absence variation in the amphidiploid Brassica napus. Issue 7 (10th January 2018) - Hurgobin, Bhavna; Golicz, Agnieszka A.; Bayer, Philipp E.; Chan, Chon‐Kit Kenneth; Tirnaz, Soodeh; Dolatabadian, Aria; Schiessl, Sarah V.; Samans, Birgit; Montenegro, Juan D.; Parkin, Isobel A. P.; Pires, J. Chris; Chalhoub, Boulos; et al.
Summary: Homoeologous exchanges (HEs) have been shown to generate novel gene combinations and phenotypes in a range of polyploid species. Gene presence/absence variation (PAV) is also a major contributor to genetic diversity. In this study, we show that there is an association between these two events, particularly in recent Brassica napus synthetic accessions, and that these represent a novel source of genetic diversity, which can be captured for the improvement of this important crop species. By assembling the pangenome of B. napus, we show that 38% of the genes display PAV behaviour, with some of these variable genes predicted to be involved in important agronomic traits including flowering time, disease resistance, acyl lipid metabolism and glucosinolate metabolism. This study is a first and provides a detailed characterization of the association between HEs and PAVs in B. napus at the pangenome level.